2003
DOI: 10.1097/00002371-200309000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Counts Independently Predict Overall Survival in Advanced Cancer Patients: A Biomarker for IL-2 Immunotherapy

Abstract: Interleukin-2 (IL-2) targets cells bearing IL-2 receptors and induces different degrees of lymphocytosis. This study retrospectively evaluated whether lymphocytosis, in addition to clinical characteristics at baseline and to tumor objective response, may predict overall survival in metastatic renal cell carcinoma patients who received IL-2 subcutaneously (s.c.). Overall survival, clinical characteristics, tumor response, and total lymphocyte count at baseline and during the first treatment cycle of 266 advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 31 publications
0
40
0
3
Order By: Relevance
“…Contrary to granulocytes, lymphocytes are involved in the elimination of cancer cells. There are reports suggesting that a decreased lymphocyte count in the peripheral blood is a predictor of poor prognosis in cancer patients [33,34]. The bottom line is that the G/L ratio reflects the status of a patient's anti-tumour immune function [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to granulocytes, lymphocytes are involved in the elimination of cancer cells. There are reports suggesting that a decreased lymphocyte count in the peripheral blood is a predictor of poor prognosis in cancer patients [33,34]. The bottom line is that the G/L ratio reflects the status of a patient's anti-tumour immune function [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that a decreased lymphocyte count in the peripheral blood is a predictor of a poor prognosis in cancer patients [27][28][29]. Bruckner et al suggested that a pretreatment absolute neutrophil count \6,000/mm3 and lymphocyte count [1,500/mm3 were independent prognostic indicators of a good prognosis for patients with metastatic gastric cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…Riesco [107] has reported that the pretreatment total lymphocyte count predicts overall survival of cancer patients, independent of other major prognostic factors. Fumgalli et al [108] have shown that lymphocyte counts independently predicts overall survival in advanced cancer patients, and should be a biomarker for interleukin-2 (IL-2) immunotherapy.…”
Section: Tumor Immunosuppression and Escape Mechanismsmentioning
confidence: 99%